Screening and validation of double allele-specific binding F-primers for the measurement of antihypertensive pharmacogenomics - Ping, Yang; Quanlin, Su; Yue, Hu; Jing, Zhang; Wenjun, Lan (Frontiers in Medicine, 2023)
Objective Previous studies have proposed that genetic polymorphisms of CYP2D6*10, ADRB1, NPPA, CYP3A5*3, ACE, CYP2C9*3 and AGTR1 involve in anti-hypertension pharmacogenomics. The purpose of this study aims to develop an amplification analysis using double allele-specific (AS) binding primers for accurate measurement of anti-hypertension pharmacogenomics.Methods For establishment of a quadruplex quantitative PCR (qPCR) analysis for genotyping of CYP2D6*10, ADRB1 (1165 G>C), NPPA (2238 T>C) and CYP3A5*3, and a triplex qPCR analysis for genotyping of ACE (I/D), CYP2C9*3 and AGTR1 (1166 A>C), mismatch AS F-primers were screened by detection of plasmid / gDNA, and validated by agreement analysis / reproducibility evaluation, in which ΔCq (differences in threshold cycles between the wild-type F-primer-based amplification assay and the mutant-type F-primer-based amplification assay) was employed to determine genotypes.Results Seven pairs of primers were successfully selected through three rounds of F-primers screening. Except of ADRB1, robustness assessment showed the amplification efficiency ranging from 0.9 to 1.1. In agreement analysis, two specimens in a training set (n=203) were defined by the triplex analysis rather than NGS as heterozygotes for ACE, which was evidenced by gel electrophoresis. Reproducibility evaluation demonstrated that the coefficient of variation (CV) was less than 5%.Conclusions The multiplex amplification analysis using screened AS binding primers is a simple, reliable and accurate tool to guide drug delivery in anti-hypertension personalized treatment.